2019
DOI: 10.1016/j.molmet.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

New roles for prokineticin 2 in feeding behavior, insulin resistance and type 2 diabetes: Studies in mice and humans

Abstract: ObjectiveProkineticin 2 (PROK2) is a hypothalamic neuropeptide that plays a critical role in the rhythmicity of physiological functions and inhibits food intake. PROK2 is also expressed in the main olfactory bulb (MOB) as an essential factor for neuro-and morphogenesis. Since the MOB was shown to be strongly involved in eating behavior, we hypothesized that PROK2 could be a new target in the regulation of food intake and energy homeostasis, through its effects in the MOB. We also asked whether PROK2 could be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…None of these genes had a highly conserved non-synonymous variant that is expected to be damaging. Foxp1 has previously been shown to regulate hepatic glucose homeostasis 45 , and insulin stimulated glucose uptake 46 , making it a strong candidate, although both Gpr27 47 , 48 and Prok2 49 also play a role in glucose related phenotypes.
Figure 7 Genome scans for select intermediary serum biochemistry measures.
…”
Section: Resultsmentioning
confidence: 99%
“…None of these genes had a highly conserved non-synonymous variant that is expected to be damaging. Foxp1 has previously been shown to regulate hepatic glucose homeostasis 45 , and insulin stimulated glucose uptake 46 , making it a strong candidate, although both Gpr27 47 , 48 and Prok2 49 also play a role in glucose related phenotypes.
Figure 7 Genome scans for select intermediary serum biochemistry measures.
…”
Section: Resultsmentioning
confidence: 99%
“…Patients with type 2 diabetes often have varying degrees of insulin resistance, and insulin resistance is associated with higher levels of inflammation and changes in lipid metabolism. 15 17 Bifidobacteria and Akkermansia detected in patients with type 2 diabetes produce short-chain fatty acids, which are inversely associated with low-grade inflammation and insulin resistance. 18 The current study found that the richness of Megasphaera was higher in the DPN group than in the NC group, and HOMA-IR was positively correlated with the presence of Megasphaera (coccidia) in the DPN group, further confirming that the occurrence of insulin resistance plays an important role in DPN associated with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…People suffering from OI might either maintain their weight, or eat less, or on the contrary eat more since food would become tasteless; reasons for this remain unclear (Croy et al, 2014). Interestingly, there is growing evidence that the olfactory system could greatly contribute in the regulation of food intake and energy balance, through its effect on sympathetic and parasympathetic tone (Palouzier-Paulignan et al, 2012;Garrison and Knight, 2017;Mortreux et al, 2019). Indeed, receptors to a variety of orexigenic and anorexigenic molecules (i.e., insulin, leptin, ghrelin, neuropeptide Y, nutrient glucose) were found in the olfactory epithelium and in the olfactory bulb (Palouzier-Paulignan et al, 2012;Min and Min, 2018).…”
Section: Effects Of Olfactory Loss On Eating Behavior Danger Warningmentioning
confidence: 99%